As faces do poder materializadas no planejamento orçamentário de uma IFES - Caliman, Douglas Roriz (2023)
The objective of the study is to explain how the faces of power manifest themselves in the budgetary process of an IFES and how they materialize power in practice. The thesis of the study establishes that the budget is not only an instrument of economic rationality, but also of power, as institutions, through their interventions and social relations, create a fertile field for power relations that cross instrumental and fiscal boundaries, as they trigger new policies and new plans. The study started from the synthesis on Organizational Power carried out by Fleming & Spicer (2014), moving on to the authors highlighted by them in each facet of power. The methodology used for the case study is qualitative and descriptive. The data was collected through documentary research, based on videos of University Council meetings, the Minutes of these meetings, Management Reports, Accountability Reports, Explanatory Notes and Ordinances. Non-participant observation was also used. The resulting data was processed and analyzed using Saldaña's Content Analysis technique (2009), with the help of the MAXQDA qualitative analysis software. The data reveal that the face of coercion materializes the exercise of power budget process through authority and pressure to force budget decisions. The face of manipulation materializes the exercise of power budget process through a biased influence to favor interests over others. The face of domination materializes the exercise of power budget process through authoritarianism incorporated in significant control over decision-making, restricting the participation and influence of others. The face of subjectivation materializes the exercise of power budget process through knowledge and constructions of discourses and ideologies, as well as surveillance that shape the way institutional actors perceive and accept budget decisions. As final considerations, firstly, the materialization of the exercise of power through coercion is more prevalent in the existence of a significant inequality of power between the actors and institutional groups involved in the budget process; secondly, that the materialization of the exercise of power through manipulation is associated with some type of political influence; thirdly, that the materialization of the exercise of power through domination occurs through the inaction of actors and institutional groups that are in a dominated position; and finally, that the materialization of the exercise of power through subjectivation occurs through emotion and strategic use of social and institutional identities. Therefore, the budget functions as an instrument of political rationality, acting as a rearranger of interests.